The Relationship Between Hemodialysis And High-Frequency Hearing Loss In Chronic Kidney Disease Patients At Dr. Wahidin Sudirohusodo General Hospital, Makassar - Syafii, Yudi L.; Kadir, Abdul; Dyah, Trining; Salam, Abdul (Journal of Neonatal Surgery, 2025)
Background: In patients with chronic kidney disease (CKD), nephron damage leads to reduced kidney excretory function, resulting in toxin accumulation, electrolyte disturbances, metabolic acidosis, and calcium metabolism disorders, all of which may affect the cationic gradient in the cochlea and disrupt auditory function. Aim: To determine the relationship between hemodialysis and highfrequency hearing loss in CKD patients at Dr. Wahidin Sudirohusodo General Hospital. Methods: A cross-sectional study involving 40 CKD subjects, with a distribution of non-hemodialysis CKD patients (n=20) and hemodialysis patients (n=20), conducted at Wahidin Sudirohusodo Hospital Makassar from January to December 2024. ENT examination and audiometry tests were performed to assess hearing thresholds. Results: The degree of hearing loss in the right ear was significantly found at 6000 Hz with an average threshold of 39.75 ± 14 dB, and at 8000 Hz with an average threshold of 47.5 ± 12.9 dB. In the left ear, it was also significant at 6000 Hz with an average threshold of 43 ± 13.51 dB, and at 8000 Hz with an average threshold of 49 ± 19.3 dB in the hemodialysis group. There is a relationship between hemodialysis and high-frequency hearing loss. Age, gender, and comorbid characteristics were not associated with hemodialysis status. Conclusion: There is a relationship between hemodialysis and high-frequency hearing loss, especially at 6000 and 8000 Hz